Analysis between Perturb & Observe Controller and Fuzzy Logic Controller for a Photovoltaic System with CUK and SEPIC Converter - Goh, H.H.; Anwar, M.S.; Chua, Q.S.; Ling, C.W.; Goh, K.C. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The power generation is using Photovoltaic (PV) cell is the best alternative developing for fossil fuel since it renewable green power, energy conservation and demand-side management. Solar energy most useful for sustainable development but due to it has a nonlinear current-voltage characteristic. It is difficult to track the maximum power produce by the PV module. This paper presents a comparison between the Single-Ended Primary-Inductor Converter (SEPIC) and CUK converter by using both Fuzzy Logic Controller (FLC) and Perturb & Observe (P&O) methods in maximum power point tracking (MPPT). In this paper, the performance, advantage and disadvantage for both converters and MPPT algorithm are described. A general model of a Photovoltaic system with proposed MPPT controller and converters is implemented in MATLAB/Simulink software. The input parameter of temperature and irradiation level will be under constant and variable level as to prove the system efficiency towards changing conditions. The simulation result will be analyzed in different case studies in order to prove the effectiveness timely response performances, efficiencies of our power of converting over input power of the PV module and the comparison of transient response of voltage ripple of the systems.